Analisis pH dan Kandungan Fitokimia Eco Enzyme dari Limbah Kulit Jeruk, Nanas, dan Mentimun - Hafiza Tara Devi; Della Rosalynna Stiadi (Lembaga Yasin AlSys, 2025)
Household waste largely consists of organic materials such as vegetable scraps, fruit peels, and leaves, which have the potential to be transformed into eco-friendly products like eco enzyme. Eco enzyme is a fermentation product of organic waste combined with palm sugar and water, which can be used as a cleaning solution, fertilizer, natural pesticide, and water quality enhancer. This study aims to examine the characteristics of eco enzyme made from pineapple, orange, and cucumber peels in both fresh and dried forms, using a mixing ratio of 3:1:10 for organic waste, palm sugar, and water, respectively. The parameters analyzed included pH, total dissolved solids (TDS), fermentation yield volume, and tannin content as a phytochemical compound. The results showed that eco enzyme from fresh waste had a pH of 3.65, TDS of 127 ppm, and a volume of 2200 ml, whereas the product from dried waste had a pH of 3.53, TDS of 235 ppm, and a volume of 1000 ml. Tannin testing using FeCl₃ reagent indicated that neither sample contained tannins. Based on these findings, it can be concluded that eco enzyme produced from both fresh and dried organic waste exhibits favorable chemical properties and is suitable for use as an environmentally friendly household cleaning solution.